Role of Soluble Urokinase-Type Plasminogen Activator Receptor in Cardiovascular Disease - Ismail, Anis; Hayek, Salim S. (Current cardiology reports, 2023)
Purpose of Review Chronic inflammation is a major contributor to cardiovascular disease (CVD) risk. Soluble urokinase plasminogen activator receptor (suPAR) is an immune-derived glycoprotein that is strongly associated with atherosclerotic disease. This review summarizes evidence on suPAR’s role in CVD pathogenesis and its potential as a prognostic indicator and therapeutic target. Recent Findings Clinical, genetic, and experimental evidence supports suPAR’s role as a pathogenic factor in atherosclerosis. suPAR promotes atherosclerosis through modulation of monocyte activation and function. Clinically, elevated suPAR levels are linked to increased cardiovascular risk across diverse populations. Ongoing clinical trials are evaluating therapies targeting suPAR signaling. Summary Current evidence positions suPAR as a regulator of myeloid cell function that contributes to vascular inflammation and subsequent cardiovascular events. Additional research is needed to determine whether suPAR measurement can improve CVD risk prediction and enable personalized management. Overall, suPAR is a promising immune-derived biomarker and target for reducing inflammation and cardiovascular risk.